Assessment score for the diagnosis of a case with pleuroparenchymal fibroelastosis - Cuneyt Tetikkurt; Bahar Kubat; Cigdem Kulahci; Seza Tetikkurt; Buket Caliskaner Ozturk (Monaldi Archives for Chest Disease, 2021)
Idiopathic pleuropulmonary fibroelastosis is an extremely rare lung disease characterized by the combination of fibrosis of the visceral pleura and the fibroelastotic changes transcending in the subpleural lung parenchyma that predominantly affects the upper lobes with accompanying volume loss. It is mostly idiopathic while infection, autoimmunity, bone marrow or lung transplantation and genetic predisposition may be associated with the development of PPFE. The disease is exceptionally rare as approximately ninety cases have been reported in the literature currently. A 35-year-old female presented with exertional dyspnea, dry cough and weight loss. Physical examination demonstrated platythorax, suprasternal notch deepening and fine rales over the upper lobes. Blood count, serum biochemistry, autoimmunity and serologic markers for collagen vascular diseases were within normal limits. Arterial blood gases demonstrated a low pO2 (48 mm Hg) and a high pCO2 (54 mm Hg) values. Chest x-ray showed bilateral parenchymal fibrotic lesions, left pneumothorax, bronchiectasis in the middle and pleural thickening in the upper lung zones while HRCT revealed bilateral apical pleural thickening, traction bronchiectasis, subpleural reticulations, ground-glass opacities and honeycombing in the upper lobes. Bronchoscopy, BAL cytology, smear and culture did not reveal any pathologic findings. Relevant with the clinical, laboratory, radiologic manifestations and the differential diagnosis with other interstitial lung diseases, PPFE was the final diagnosis. The aim of this case report was to present the clinical manifestations of our case. The second crucial objective was to establish a diagnostic scoring system relevant with the literature and the clinical manifestations of the patient.